2020
DOI: 10.1590/1519-6984.210489
|View full text |Cite
|
Sign up to set email alerts
|

Cytoarchitecture of the superior olivary complex of three neotropical species of bats (Noctilio leporinus, Phyllostomus hastatus and Carollia perspicillata) with different foraging behavior

Abstract: Abstract The understanding of the echolocation by studying different auditory nuclei of echolocating bats can be an important link in elucidating questions arising in relation to their foraging behavior. The superior olivary complex (SOC) is the primary center for processing the binaural cues used in sound localization since echo locating bats rely on acoustic cues to navigate and capture prey while in flight. The present study was taken to test the hypothesis that the SOC of echolocating neotropical b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 28 publications
(38 reference statements)
2
5
0
Order By: Relevance
“…The MNTB appeared large in size, extending medially to the raphe and penetrated by most of the fibres of passage in all the bats studied. The auditory nuclei are relatively larger in echolocating animals like the marmoset (Prado Reis and Abrantes Erhart, 1979), dolphins (Thomas et al, 2004;DeLong et al, 2007) and bats (Zook and Casseday, 1982;Gibbons et al, 2013aGibbons et al, , b, 2019Adogwa et al, 2014;Gibbons et al, 2019) than the human and non-human primates (Neuweiler and Covey, 2000) which is similar in the present study. The very well developed MNTB in N. leporinus (1160 ± 124 μm in length) indicated that this bat heavily depends on the echolocation than the two other bats studied.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The MNTB appeared large in size, extending medially to the raphe and penetrated by most of the fibres of passage in all the bats studied. The auditory nuclei are relatively larger in echolocating animals like the marmoset (Prado Reis and Abrantes Erhart, 1979), dolphins (Thomas et al, 2004;DeLong et al, 2007) and bats (Zook and Casseday, 1982;Gibbons et al, 2013aGibbons et al, , b, 2019Adogwa et al, 2014;Gibbons et al, 2019) than the human and non-human primates (Neuweiler and Covey, 2000) which is similar in the present study. The very well developed MNTB in N. leporinus (1160 ± 124 μm in length) indicated that this bat heavily depends on the echolocation than the two other bats studied.…”
Section: Discussionsupporting
confidence: 84%
“…Since the different bats forage different environment, it is assumed that different foraging strategies reflect on morphology of the MNTB, an important nucleus in sound localization pathway. Though few studies were done on comparative cytoarchitecture of the various auditory nuclei of echolocating bats with different foraging strategies (Gibbons et al, 2013a(Gibbons et al, , b, 2019Adogwa et al, 2014), the MNTB was not studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, these bats possess a well‐developed MSO that is homolog to the MSO in non‐echolocating mammals with some differences in connectivity pattern and function in acoustic contrasting (Casseday & Pollak, 1988; Grothe et al, 1994; Pollak & Casseday, 1988). Anatomical differences in the SOC among echolocating bat species are thought to be linked to differences in feeding strategy and echolocation strategies (Gibbons et al, 2019; Zook & Casseday, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…The size of the LSO was proposed to be correlated to the hearing range exploited by an animal (Moore, 2000; Schwartz, 1992). Generally, LSO and MNTB are well developed in mammals with good high frequency hearing and are especially prominent in echolocating bats and odontocetes (Gibbons et al, 2019; Grothe et al, 2010). The volume of the LSO in D. delphis (average 150 mm 3 ) is the largest for any mammal measured so far and could reflect the dolphins' adaptation to high frequencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation